2006
DOI: 10.1097/01.tp.0000235533.29300.e7
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistance Protein 2 Genetic Polymorphisms Influence Mycophenolic Acid Exposure in Renal Allograft Recipients

Abstract: The MRP2 C-24T and C-3972T polymorphisms protect renal transplant recipients from a decrease in MPA exposure associated with mild liver dysfunction. Furthermore, this study suggests that the C-24T SNP is associated with a lower oral clearance of MPA in steady-state conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(137 citation statements)
references
References 56 publications
4
129
4
Order By: Relevance
“…CYP3A5*3 (6986A4G (rs776746)) and SLC22A1 (156T4C (rs1867351), 480G4C (rs683369), 1022C4T (rs2282143) and 1222A4G (rs628031)) genotyping was performed by PCR-RFLP, as previously described by Fukuen et al 34 and Itoda et al, 25 respectively. Similarly, ABCC2 (À24C4T (rs717620)) and ABCB1 (1236T4C (rs1128503), 2677G4T/A (rs2032582) and 3435T4C (rs1045642)) were genotyped as described by Naesens et al, 35 Wu et al, 36 Tanaka et al 37 and Cascorbi et al, 38 respectively. ABCG2 421C4A (rs2231142) was genotyped as described by Kobayashi et al, 39 and SLCO1B3 (334T4G (rs4149117)) as described by Tsujimoto et al 40 All genotype frequencies were tested for Hardy-Weinberg equilibrium.…”
Section: Measurement Of Plasma Im Concentrationmentioning
confidence: 99%
“…CYP3A5*3 (6986A4G (rs776746)) and SLC22A1 (156T4C (rs1867351), 480G4C (rs683369), 1022C4T (rs2282143) and 1222A4G (rs628031)) genotyping was performed by PCR-RFLP, as previously described by Fukuen et al 34 and Itoda et al, 25 respectively. Similarly, ABCC2 (À24C4T (rs717620)) and ABCB1 (1236T4C (rs1128503), 2677G4T/A (rs2032582) and 3435T4C (rs1045642)) were genotyped as described by Naesens et al, 35 Wu et al, 36 Tanaka et al 37 and Cascorbi et al, 38 respectively. ABCG2 421C4A (rs2231142) was genotyped as described by Kobayashi et al, 39 and SLCO1B3 (334T4G (rs4149117)) as described by Tsujimoto et al 40 All genotype frequencies were tested for Hardy-Weinberg equilibrium.…”
Section: Measurement Of Plasma Im Concentrationmentioning
confidence: 99%
“…1 In vitro experiments but also in vivo studies showed that the 5 0 -UTR SNP À24C4T, which is strongly linked to the silent SNP 3972C4T, seems to be associated with a decreased function of the transporter; À24C4T reportedly lowers the clearance of mycophenolic acid in renal allograft recipients and methotrexate in pediatric acute lymphoblastic patients. [2][3][4] In non-cancerous renal cortex tissue À24C4T showed a significant decreased mRNA expression. 5 Non-small lung cancer patients exhibiting the variant allele showed a higher response to irinotecan therapy suggesting a higher bioavailability for this anti-neoplastic drug.…”
Section: Introductionmentioning
confidence: 98%
“…with C-24T [18] or with other SNPs in ABCC2 gene that form different ABCC2 haplotypes [19]. Our hypothesis was that raloxifene and / or its glucuronides might be substrates for ABC transporters, from which we selected the ones that were most frequently associated with significant impact on pharmacokinetics of various other drugs, namely, Pgp, MRP1, MRP2, MRP3 and BCRP.…”
Section: Discussionmentioning
confidence: 99%
“…The tested polymorphisms were chosen on the basis of variant allele frequencies that were 46.0%, 32.1% and 9.5% for ABCB1 c.3435C>T [31], ABCC2 c.3972C>T [18] and ABCG2 c. 421C>A [32], respectively. Due to a relatively small number of study participants and low allelic frequency the genotyping for ABCG2 c. 421C>A 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 was not performed.…”
Section: Patient's Genotype Frequenciesmentioning
confidence: 99%
See 1 more Smart Citation